2008
DOI: 10.1093/europace/eun240
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of implantable cardioverter-defibrillators: implications for clinical practice and health care systems

Abstract: Battery longevity is significantly different among manufacturers. ICD cost is strictly dependent on device longevity, whereas device up-front cost is of limited clinical meaning. Appropriate assessment of cost-effectiveness should be based on ICD longevity in the real-life scenario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 36 publications
6
51
1
Order By: Relevance
“…In agreement with previous reports, 12,26 device replacements for battery depletion started to occur after 3 years of follow-up and involved 50% of CRT-D patients after 4 years at Kaplan-Meier analysis. Previous data from a large US registry showed that 53% of normally performing ICDs and, specifically, only 4% of CRT-D were in service 4 years after implantation.…”
Section: Device Longevitysupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with previous reports, 12,26 device replacements for battery depletion started to occur after 3 years of follow-up and involved 50% of CRT-D patients after 4 years at Kaplan-Meier analysis. Previous data from a large US registry showed that 53% of normally performing ICDs and, specifically, only 4% of CRT-D were in service 4 years after implantation.…”
Section: Device Longevitysupporting
confidence: 91%
“…27 In our series, battery depletion represented the main cause of earlier surgical revision in patients with CRT-D. Indeed, it has been shown that CRT-D are the most demanding antiarrhythmic devices in terms of battery consumption because of the need for continuous biventricular pacing, although device longevity may differ significantly among manufacturers 12,26 and modern algorithms for pacing output reduction have been demonstrated to improve longevity. 28 Nevertheless, the risk of earlier surgical revision for battery depletion in CRT-D should be considered not only per se, but also in relationship with the observed higher risk of infection following replacement.…”
Section: Device Longevitymentioning
confidence: 90%
“…According to our modelling results, extending longevity translates into a reduction in device replacements, hospitalizations, and complications, as well as reduced costs. Admittedly, these data are derived from a model based on data from other studies, 9,27 which is no replacement to validation and confirmation in the real-world setting, where other factors, such as co-morbidities, lead failure, and device recalls add to the complexity of device therapy. It is worth to promote the institution of registries for collecting independent data on actual device longevity, thus avoiding the obvious limitation of data obtained from single institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis probably underestimated another source of saving, that is, the potential lengthening of follow-up visits due to longer-lasting devices. 27,34 In fact, independently from device longevity we assumed a background number of two follow-up visits per year after the first implant. This amount was considered to rise to three follow-up visits during the year of replacement (one more follow-up visit).…”
Section: Discussionmentioning
confidence: 99%
“…Between 2008 and 2014 several studies had been published on the problem of ICD longevity in clinical scenarios. These analyses included ''older'' and currently used ICD devices [9][10][11][12][13][14][15]. In the study by Biffi et al [9] 153 ICD replacements of three different brands were analyzed.…”
Section: Icd Device Technologymentioning
confidence: 99%